(untitled) (Journal of Educational Sciences, 2019)
In the article the researchers analyze the foreign experience of the organization and methodology of inclusive education. On the basis of scientific positions of Great Britain, Canada, the USA, Russia and other countries scientists the basic tendencies of development of inclusive education abroad are revealed. Inclusive education is a complex process that requires a certain transformation of the usual way of the educational environment, certain social and educational conditions, which allow essentially implementing different approaches and methods to include people with special educational needs (SEN) in the educational space. In solving this social problem, it is important to improve the quality of professional training of specialists, in particular social pedagogues. It is revealed that important trends of inclusive education abroad are: (1) focus on the formation of an inclusive culture in the educational institution, the development of the philosophy of inclusion in general; (2) coordination of activities of all participants of education, the inclusion of parents in an inclusive educational process for maximum assistance to children with special educational needs; (3) special training of pedagogues to work in conditions of inclusive education and team training; (4) support of an inclusive school by its partners and assistants acting by various public organizations and psychological and pedagogical services; (5) individualization of the educational program for inclusion of children with SEN in the educational process and development of an individual plan of their training. Key words: inclusive education, inclusion, special educational needs, atypical children, students with disabilities, integrated learning.